Emotional intelligence why it can matter more than IQ - Goleman, Daniel (New York Bloomsbury Publishing, 2020)
Does IQ define our destiny? In his groundbreaking bestseller, Daniel Goleman argues that our view of human intelligence is far too narrow. It is not our IQ, but our emotional intelligence that plays a major role in thought, decision-making and individual success. Self-awareness, impulse control, persistence, motivation, empathy and social deftness: all are qualities that mark people who excel, whose relationships flourish, who can navigate difficult conversations, who become stars in the workplace.
Includes Index
Keywords: Emotions